Atrial fibrillation and heart failure-associated remodeling of two-pore-domain potassium (K2P) channels in murine disease models: focus on TASK-1 - Wiedmann, Felix Tobias; Gomes Botelho Quintas, Bruna; Ratte, Antonius; Thomas, Dierk; Katus, Hugo; Schmidt, Constanze (Basic research in cardiology, 2018)
Understanding molecular mechanisms involved in atrial tissue remodeling and arrhythmogenesis in atrial fibrillation (AF) is essential for developing specific therapeutic approaches. Two-pore-domain potassium (K2P) channels modulate cellular excitability, and TASK-1 (K2P3.1) currents were recently shown to alter atrial action potential duration in AF and heart failure (HF). Finding animal models of AF that closely resemble pathophysiological alterations in human is a challenging task. This study aimed to analyze murine cardiac expression patterns of K2P channels and to assess modulation of K2P channel expression in murine models of AF and HF. Expression of cardiac K2P channels was quantified by real-time qPCR and immunoblot in mouse models of AF [cAMP-response element modulator (CREM)-IbΔC-X transgenic animals] or HF (cardiac dysfunction induced by transverse aortic constriction, TAC). Cloned murine, human, and porcine TASK-1 channels were heterologously expressed in Xenopus laevis oocytes. Two-electrode voltage clamp experiments were used for functional characterization. In murine models, among members of the K2P channel family, TASK-1 expression displayed highest levels in both atrial and ventricular tissue samples. Furthermore, K2P2.1, K2P5.1, and K2P6.1 showed significant expression levels. In CREM-transgenic mice, atrial expression of TASK-1 was significantly reduced in comparison with wild-type animals. In a murine model of TAC-induced pressure overload, ventricular TASK-1 expression remained unchanged, while atrial TASK-1 levels were significantly downregulated. When heterologously expressed in Xenopus oocytes, currents of murine, porcine, and human TASK-1 displayed similar characteristics. TASK-1 channels display robust cardiac expression in mice. Murine, porcine, and human TASK-1 channels share functional similarities. Dysregulation of atrial TASK-1 expression in murine AF and HF models suggests a mechanistic contribution to arrhythmogenesis.